Analisis Konflik Moral dan Spiritual dalam Film "Tuhan Izinkan Aku Berdosa" - M. Dzakwan Adriana; Hima Qonita Desikha; Adhi Kusuma (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
The film Tuhan Ijinkan Aku Berdosa presents an in-depth description of moral and spiritual conflict through the inner turmoil experienced by the main character. This abstract explains that the factors underlying the conflict are complex and interrelated, including psychological conditions, social backgrounds, and religious aspects that underlie the lives of the characters. Conflict does not only arise from external events, but also as a result of the clash between values that are normatively believed by a Muslim and the reality of life that takes actions that deviate from Islamic teachings. The main character grew up in a stressful environment, marked by poverty and social alienation, so that he felt he had no other choice but to take a path that was considered morally wrong. A deep sense of guilt also emerged as a consequence of behavior that was contrary to religious values, which then triggered a spiritual conflict that further complicated his inner state. In addition, a weak understanding of religious teachings and a lack of spiritual guidance also played an important role in exacerbating the conflict. When individuals grow up without strong religious direction or feel alienated from the religious community, they tend to seek meaning and salvation in deviant ways, thus becoming further from the path that is approved by God.